Gender equality: A study of female participation in management roles in auditing firms in Brazil - Carneiro, Luziberto Barrozo; Santos, Thais Helen Andrade (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: The female presence in the business world has been growing, however there are still several obstacles to achieving equal opportunities in management roles. Women have low representation in management roles, especially high-ranking ones. This study was carried out to analyze female representation in management roles in auditing firms in Brazil. Purpose: This study analyzes female representation in leadership positions in Big Four auditing firms in Brazil between the period 2016-2023. Method: In this sense, documentary research was carried out, inspecting the GRI Sustainability Reports of these organizations. Information about the programs developed that contribute to the rise of women in the role of leader was also sought through the companies' websites. Results: The results demonstrated that female representation, especially in the role of partner, is still low when compared to male representation, although it has evolved in the years analyzed, progressing from 16% (2016) to 25% (2023) in the case of the firm EY and 16% (2016) to 26% (2023) at KPMG. The Big Four initiated gender equity and female talent development policies. Conclusions: It is concluded that the Glass Ceiling is still present in these organizations and is being gradually deconstructed.